2009
DOI: 10.5539/ies.v2n4p182
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Responses Through Verbal Discourse in the Reading of Literary Texts

Abstract: The past decade has viewed the important role literature plays in enhancing the learning process among students in Malaysian English classrooms. However, most English teachers in particular are not prepared to teach literature due to the lack of training and exposure on the subject. This paper seeks to explore the ways teacher trainees from one teacher training institute attempt to provide multiple responses on two Malaysian short stories through verbal discourse. This qualitative study uses the transcripts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, the use of visual aids like pictures, videos and projectors encourage students to read texts with interest, which make it easier for them to understand technically complicated words (4). This proves the use of visual aids act as 'vehicles' that can be used to enrich and enhance the act of reading and consequently, the use of multimedia applications for language teaching and learning, it has been stated that the insertion of visual aids in teaching enables authentic communication between students and written contexts (18,184). Besides, the insertion of animation of texts and graphics in the webbased multimedia as a tool to teach Russian language increases students' interest in learning and watching documentary films.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, the use of visual aids like pictures, videos and projectors encourage students to read texts with interest, which make it easier for them to understand technically complicated words (4). This proves the use of visual aids act as 'vehicles' that can be used to enrich and enhance the act of reading and consequently, the use of multimedia applications for language teaching and learning, it has been stated that the insertion of visual aids in teaching enables authentic communication between students and written contexts (18,184). Besides, the insertion of animation of texts and graphics in the webbased multimedia as a tool to teach Russian language increases students' interest in learning and watching documentary films.…”
mentioning
confidence: 93%
“…As we analyzed the 9 th question according to the method research, we found out that option (a) was chosen by sixteen participants (100%) during the interview (a) roleplay. In a study, it is observed that teachers are very pleased with using multimedia elements, and they think that this experience is interesting, motivating and contribute to their education (1,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Some advantages of multimedia elements are following.…”
mentioning
confidence: 99%